Risk Factors of Preinvasive and Invasive Cervical Cancer - Shrestha, P; Koirala, P; Singh, M (Nepal Journal of Obstetrics and Gynaecology, 2016)
Aims: The objective of this study was to assess the risk factors of preinvasive and invasive cervical cancer. Methods: This was a prospective hospital based case control study conducted from April 2012 to April 2013, which included 91 patients in each group. Among cases, 34 were Cervical Cancer and 57 were Cervical Intraepithelial Neoplasia. Simple random method was adopted for selecting patients. Prefixed questionnaire was used. Statistical analysis was done using SPSS 19.0. Results: In multivariate analysis, history of abnormal vaginal discharge and cigarette smoking were significantly associated with cervical cancer (p value of 0.001 and 0.003 respectively) and Cervical Intraepithelial Neoplasia (p <0.001). Whereas, early age at first sexual intercourse ≤ 16 years and more than one sexual partner of husband had only borderline significance for Cervical cancer (p value 0.049 and 0.038 respectively). Conclusions: Cigarette smoking and abnormal vaginal discharge were significantly associated with cervical cancer.